Nitric oxide promotes rapid development of motility to accelerate biofilm dispersal in Vibrio cholerae - Nathaniel C. Esteves; Ran Tao; Qinqin Pu; Arkaprabha Banerjee; Arnold J. T. M. Mathijssen; Jun Zhu (Proceedings of the National Academy of Sciences, 2025)
Bacterial biofilms are resilient multicellular communities that underlie persistent infections and environmental survival. Dispersal from biofilms is a pivotal event for transmission and pathogenesis, yet the host signals and bacterial mechanisms orchestrating this transition remain poorly understood. Here, we show that nitric oxide (NO), a ubiquitous host-derived signaling molecule, acts as a rapid trigger for biofilm dispersal in Vibrio cholerae , a highly motile gram-negative bacterium and the etiologic agent of cholera, by promoting the development of motility. NO exposure induces broad upregulation of flagellar biosynthesis genes, increases flagellin production, and reduces intracellular cyclic-di-GMP levels, thereby priming aflagellated biofilm-associated cells for active swimming and dispersion. Using single-cell imaging in custom microfluidic devices, we directly visualize NO-stimulated biofilm detachment and development of robust swimming motility within minutes. In vivo, biofilm-derived V. cholerae colonize more efficiently in NO-rich environments, and NO produced by epithelial cells enhances bacterial detachment from epithelial surfaces. Our findings reveal a host–pathogen interface in which NO serves as a morphogenetic cue, orchestrating the rapid transition from sessility to motility.